A Call for Re-Evaluation Prior Tax Treaty Relief Application (Philippine Law Journal, 2014)
This article examines the administrative procedures and requirements imposed by the Bureau of Internal Revenue for taxpayers to be able to avail themselves of reliefs provided under applicable tax treaties. In particular, this article looks at and assesses the prevailing system of andatory prior applications for tax treaty relief and tax rulings in light of the international obligations of the Philippines under various treaties. This article posits that, despite the laudable objectives of the prevailing system as regards procedural efficiency and streamlined service, the substantive rights of taxpayers under international treaties are effectively impaired and overridden, in violation of international.